Legal Consequences of Differences in Transaction Values in Land Sales and Purchase Deeds and the Real Prices Before The Land Deed Official - Moertihari, Safira Karenina; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to determine and analyze the legal consequences arising from the difference in transaction value in the land sale and purchase deed with the real price before the Land Deed Making Officer and to determine and analyze the legal responsibility for the Land Deed Making Officer (PPAT) for the difference in transaction value with the actual price in the Sale and Purchase Deed (AJB). This study is an empirical normative legal research, namely legal research on legal norms, legal practices and also common legal behaviors and finding legal opinions and explaining legal realities that are descriptive and value-free. The formulation of the problem that the researcher took was what are the legal consequences of the sale and purchase deed made by the PPAT related to the difference in the price that is not actual and what are the legal consequences of the sale and purchase deed that does not correspond to the real price. The results of the study explain that the validity of the Sale and Purchase Deed (AJB) made by the Land Deed Making Officer (PPAT) related to the difference in the price that is not actual causes the deed to be legally flawed. Legal consequences The difference in transaction value in the land sale and purchase deed with the real price gives rise to legal consequences in the fields of taxation and criminal law. Keywords: Differences in Transaction Value; Land Deed Making Officials; Land Sale and Purchase Deeds; Legal Consequences; Real Price.